Pengaruh Implementasi Dana Bantuan Operasional Sekolah (BOS) Dan Manajemen Berbasis Sekolah (MBS) Terhadap Kepuasan Orang Tua Siswa Selaku Pengguna Layanan Di SMP Negeri Kabupaten Sukabumi - Heri Hermawan (LPPM AMIK Citra Buana Indonesia, 2018)
Research conducted in SMP District of Sukabumi. This Research aim to know 1) Influence Of Implementation Relief Fund Operational School (BOS) to Satisfaction of Consumer Of Service 2) Influence Of Implementation School Based Management (MBS) to Satisfaction of Consumer Of Service 3) Influence Of Implementation Relief Fund Operational School ( BOS) and School Based Management ( MBS) by together to Satisfaction of Consumer of Service. This Research entangle 396 taken student parent as sampel by using Method of cluster proporsional. This method used because researcher do not have framework of sampel good, its amount population very big difficult to so that use random method and heterogeneous assumed population according to certain characteristic before hand in a few population sub. Elementary of determination of strata of subpopulasi this determined pursuant to geographical position, this matter because very broadness spreading of research region in district of Sukabumi. Intake of data conducted with interview, survey, FGD (Focus GroupDiscussion) and document study. Data-Processing research conducted by using technique of regresi and correlation. Result of research : First, Analysis Correlation Variable X1, X2 and Y look that variable X1 (0,531) owning strong relation with variable X2 ( 0,584) and also with variable Y, this matter with larger ones number from 0,5. its Probability value that variable X1 and X2 by significant have strong correlation variable Y, this matter because its value smaller than 0,05 that is 0,000.Second, analysis regresi correlation and with prediktor (constant) X1, X2 together to Y, strong relation where coefficient value R equal to 0,587 with coefficient of determinasi ( Square R) 0,344 with the meaning 34,4 % satisfaction of student parent as consumer of education service determined by BOS fund implementation and MBS. While the rest 65,6% determined by other factor. For the prediktor X2 to strong Y relation also with value of R 0,584 and determinasi koefisian ( Square R) 0,341. Adjusted R square 0,339 with standard of error 5,08696. Durbin-Watson 0,528 symptom inexistence of autokorelasi do not there are mistakes of resulted from intruder research because number 0,528 residing in among - 2 and 2. Third, F test for the prediktor X1, X2 obtained F calculate equal to 103,252 with storey;level of signifikan 0,000. While for the prediktor of X2 obtained F calculate equal to 203,820 with level of signifikan its 0,000 meaning the two owning probability much more small from 0.05. this matter show that BOS implementation ( X1) and MBS ( X2) by together have an effect on to satisfaction of student parent as consumer of education service SMPN district of Sukabumi.Fourth, from result of variable coefficient test ( test t) X1 and X2, in the reality variable of X1 number show of signifikan 0,147, this number bigger than 0,05 so that variable of X1 this released from equation of regresi, while Variable X2 have value of signifikan ( less than 0,05) matter this means that only variable of X2 giving real influence (signifikan) to variable of Y . Equation of X2 regresi to Y can be compiled as follows : Y = 11,114 + 0,776X2.